2010
DOI: 10.1002/mmce.20479
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of mutual coupling of arbitrary order in coupled circuits and array antennas

Abstract: This article presents a fundamental strategy for accurately modeling the mutual coupling of arbitrary order in any large-scale electromagnetic structures and high-density integrated chips such as antenna array elements and coupled circuit elements. The proposed method starts from the modeling of the first-order mutual coupling, and it consists of two main steps. First of all, an equivalent circuit model describing low-order mutual coupling (adjacent coupling) is characterized and established, of which each par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The mutual currents may be calculated from the mutual impedance matrix by employing the concept of a twoport network as given in ( 4) and (5).…”
Section: Overview Of the Patmentioning
confidence: 99%
See 4 more Smart Citations
“…The mutual currents may be calculated from the mutual impedance matrix by employing the concept of a twoport network as given in ( 4) and (5).…”
Section: Overview Of the Patmentioning
confidence: 99%
“…3,4 The performance of the antenna array degrades severely due to the presence of mutual coupling among the array elements, which causes an impedance mismatch, deviation of the radiation pattern, distortion and so forth. 2,5 A significant number of research works have been reported for the optimal radiation pattern synthesis of the concentric circular antenna array (CCAA), [6][7][8][9][10][11] where mutual coupling effect is not considered for the design purpose; hence, those results are not practically suitable. However, in this article, authors have employed the method of parametric assimilation technique (PAT) 12 for the correction of mutual coupling affected erred radiation pattern to the desired radiation pattern by using evolutionary optimisation techniques.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations